Забезпечення послуг IoT 5G - Сушко, Ю. В. (ХНУРЕ, 2019)
The Internet of Things is a worldwide physical network in which all services can be connected and remotely controlled. As more and more devices are equipped with RFID or smart sensors, connecting "things" is becoming more simple. At the sensing level, wireless 5G smart systems with tags or sensors can now automatically be recognized and exchange information with various devices.